DEPRECIATION–DOES IT RELATE TO ORIGINAL COST OR TO COST OF REPLACEMENT? - Tilly, Virgil S. (The Accounting Review, 1958)
Abstract As accountants, our responsibility is to report on the trusteeship of management. Management in turn should not be charged with accountability for assets and liabilities or for the determination of income on a basis other than the basis of the actual assets that were placed in use and consumed in operations. Furthermore, as accountants, we should firmly resist efforts to confuse accounting principles with devices to secure increased rates for a utility or to obtain income tax deductions. An accounting principle is supposed to apply with equal fairness and reasonableness in all situations where applicable, whereas a device is simply an expediency for a special situation. Historical cost of assets is not a fetish as some assert, but it is the actual basis on which management does its planning and operates the enterprise. Is not depreciation then the amortization of a capital expenditure that represents a charge to income of the actual cost of the expenditure over the useful life of the asset represented thereby? How can depredation with fairness and reasonableness be anything else than that?